Eksplorasi Konsep Falah Perspektif Umer Chapra - Syamsuri; Nurul Rahmania; Ardiyanti (Yayasan Literasi Sains Indonesia, 2022)
The main focus of this research is to discuss the concept of M. Umer Chapra's thought in the world of economics. This study uses a qualitative-descriptive approach with library research techniques (Library Research). The results of the study show that M. Umer Chapra's thoughts in the field of economics have formulated many religious, traditional to modern sciences. Among the many concepts of thought, the concepts of falah, hayyah thayyibah, and economic obstacles for Muslims are still interesting discussions to be studied. From his theory of economic thought, Umer Chapra puts forward moral intensity as the most important thing to be taken into account. Because morality is the key to the life goals of falah and hayyah thayyibah. As well as being able to deliver a fair Islamic economy in the socio-economic field, so that it becomes a means of solving the failure of the Socialist and Capitalist economies.